2023
DOI: 10.3390/ani13061103
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Pathogenesis of Red Mark Syndrome in Rainbow Trout (Oncorhynchus mykiss) through an Integrated Morphological and Molecular Approach

Abstract: Red mark syndrome (RMS) is a widespread skin disorder of rainbow trout in freshwater aquaculture, believed to be caused by a Midichloria-like organism (MLO). Here, we aimed to study the pathologic mechanisms at the origin of RMS by analyzing field samples from a recent outbreak through gene expression, MLO PCR, quantitative PCR, and a histopathological scoring system proposed for RMS lesions. Statistical analyses included a One-Way Analysis of Variance (ANOVA) with a Dunnett’s multiple comparisons test to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…With regard to the histological characterization of wounds, our findings agree with previous works ( Figure 1 and Figure S1 ). An inflammatory response was observed, which, depending on the degree of progression of the lesion, was extended from the dermis to the hypodermis, accompanied by a significant loss of scales and leukocyte infiltration [ 4 , 5 , 26 , 27 ]. The observed inflammatory response indicates the activation of an innate immune response in the lesions [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…With regard to the histological characterization of wounds, our findings agree with previous works ( Figure 1 and Figure S1 ). An inflammatory response was observed, which, depending on the degree of progression of the lesion, was extended from the dermis to the hypodermis, accompanied by a significant loss of scales and leukocyte infiltration [ 4 , 5 , 26 , 27 ]. The observed inflammatory response indicates the activation of an innate immune response in the lesions [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The condition of SD or RMS in rainbow trout appears to be horizontally transmissible, and according to the current literature [ 4 , 5 , 45 ], a bacterial infection is considered the potential etiology, with Rickettsia-like organisms deemed the most probable candidate. Additional research revealed a strong and positive correlation between fish affected by RMS and an RLO identified as a Midichloria-like organism (MLO), belonging to the Midichloriaceae family and the order Rickettsiales [ 4 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations